A composite wall insulation block with low thermal conductivity and preparation method thereof

By using recycled concrete blocks, aerogel insulation materials and foamed ceramic plates in composite wall insulation blocks, combined with polyethylene fibers and basalt fibers, the high thermal conductivity, compression resistance and disassembly resistance in the prior art is solved. The poor and poor water resistance effect have achieved better thermal insulation and water resistance.

CN118668861BActive Publication Date: 2025-01-07南通固盛建材有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410710493.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-01-07
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The existing composite wall insulation blocks have problems such as high thermal conductivity, waste of resources, poor compressive and dismantling capabilities, and poor water resistance.

Method used

Recycled concrete blocks combine aerogel insulation material and foamed ceramic plates. By setting insulation tanks and cavity in the blocks, adding aerogel insulation material and foamed ceramic plates, and reinforced using polyethylene fibers and basalt fibers. Material, combined with slag micro powder modifier and polyvinyl alcohol modifier to improve crack resistance and waterproofing properties.

Benefits of technology

It significantly reduces the thermal conductivity, improves fire resistance and heat preservation, extends service life, enhances compressive and disassembly resistance, and improves permeability and water resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118668861B_ABST
    Figure CN118668861B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite wall insulation block with low thermal conductivity and a preparation method thereof, which relates to the technical field of composite wall insulation blocks, and includes a recycled concrete block, a heat preservation groove is provided in the middle of the top of the recycled concrete block, an aerogel heat preservation material is installed on the inner wall of the heat preservation groove, a plurality of cavities are provided on the outer side of the top of the recycled concrete block, a foamed ceramic plate is installed on the inner wall of the cavity, and connection holes are provided at the four corners of the top of the recycled concrete block. The present invention adds aerogel heat preservation material and foamed ceramic plate into the heat preservation groove and the cavity through the arrangement of recycled concrete blocks, heat preservation grooves and cavities, the aerogel heat preservation material has low thermal conductivity, is waterproof and non-flammable, and also has the effects of sound insulation and shock absorption, and the foamed ceramic plate has low thermal conductivity and non-combustion effects, thereby being able to reduce the thermal conductivity of the heat preservation block and improve the fire prevention and heat preservation effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite wall insulation blocks, in particular to a composite wall insulation block with low thermal conductivity and a preparation method thereof. Background Art

[0002] Walls mainly include load-bearing walls and non-load-bearing walls, which mainly play the role of enclosure and separation of space. Walls need to have sufficient strength and stability during use. With the development of the construction industry, in order to increase the construction speed, masonry blocks are used. Masonry blocks are man-made blocks used for masonry and are a new type of wall material. Their appearance is mostly right-angled hexahedrons, which have the advantages of simple equipment and fast masonry speed.

[0003] The defects of existing composite wall insulation blocks are:

[0004] 1. Patent document US09175469B2 discloses self-reinforcing blocks, walls made of self-reinforced blocks, and a method for making self-reinforced blocks. However, the above document lacks a substance that can reduce the thermal conductivity during the preparation process, and there is a technical problem of high thermal conductivity.

[0005] 2. Patent document US08806824B2 discloses that the wall construction and components are the same, but the selection and use of materials in the above document not only easily lead to waste of resources, but also the insulation materials are easily damaged, resulting in a technical problem of poor insulation effect;

[0006] 3. Patent document KR101830354B1 discloses the use of the same wall construction and building wall, but the blocks in the above document have poor compression and demolition resistance, which easily leads to the technical problem of a low service life of the prepared building;

[0007] 4. Patent document CN104402493B discloses a steam-free self-insulating building block and a preparation method thereof. However, the insulating building block prepared in the above document has fine cracks on its surface. When in use, especially on rainy days, rainwater will penetrate, and there is a technical problem of poor water resistance. Summary of the invention

[0008] The object of the present invention is to provide a composite wall insulation block with low thermal conductivity and a preparation method thereof, so as to solve the technical problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a composite wall insulation block with low thermal conductivity, comprising a recycled concrete block, a heat preservation groove is opened in the middle of the top of the recycled concrete block, and an aerogel heat preservation material is installed on the inner wall of the heat preservation groove;

[0010] A plurality of cavities are provided on the outer side of the top of the recycled concrete block, and a foamed ceramic plate is installed on the inner wall of the cavity. Connection holes are provided at the four corners of the top of the recycled concrete block, and connection blocks are installed at the four corners of the bottom of the recycled concrete block, and the inner wall of the connection hole is connected to the outer wall of the connection block;

[0011] Another group of recycled concrete blocks are installed on the top, bottom, front and side of the recycled concrete block through mortar, and an insulation wall is set by multiple groups of recycled concrete blocks. Waterproof layers are installed on one side and the other side of the recycled concrete block. The outer wall of the waterproof layer on the other side of the recycled concrete block is installed with a wear-resistant protective layer. A group of slots are opened on the front of the recycled concrete block, and a group of blocks are installed on the back of the recycled concrete block, and the inner wall of the slot is movably connected to the outer wall of the block.

[0012] Preferably, the steps for preparing the composite wall insulation block with low thermal conductivity are as follows:

[0013] S1. Obtain raw materials for composite wall insulation blocks with low thermal coefficient, wherein the weight proportions of the raw materials are 50-70 parts of recycled aggregate, 30-45 parts of natural aggregate, 1-3 parts of polyethylene fiber, 20-25 parts of expansion agent, 0.5-1 parts of dispersant, 45-68 parts of cement, 22-28 parts of water, 1-3 parts of water reducing agent, 10-16 parts of slag micro powder modifier, 10-16 parts of polyvinyl alcohol modifier, 1-3 parts of basalt fiber, 13-18 parts of ceramic fragments, 1-2 parts of adhesive and 10-15 parts of nano-silica aerogel;

[0014] S2, grinding and crushing the recycled aggregate to obtain small particles, soaking the obtained particles in a slag micropowder modifier for 1 hour and then taking them out to air-dry, and then soaking the air-dried particles again in a polyvinyl alcohol modifier for 1 hour and then taking them out to air-dry, thereby obtaining the modified recycled aggregate;

[0015] S3, shearing and crushing the polyethylene fiber and the basalt fiber respectively to obtain short-cut polyethylene fiber and short-cut basalt fiber, and mixing and stirring the obtained short-cut fiber with an expansion agent and a dispersant to obtain a composite fiber anti-cracking agent;

[0016] S4, putting the recycled aggregate obtained in S2 and the natural aggregate into a mixing machine, mixing and stirring, and obtaining a mixture A;

[0017] S5, mixing the composite fiber anti-cracking agent obtained in S3 with the mixture A obtained in S4, thereby obtaining a mixture B;

[0018] S6, adding cement, water and a water reducing agent to the mixture B obtained in S5, mixing and stirring, and thereby obtaining a recycled concrete material;

[0019] S7. Use recycled concrete materials to make recycled concrete blocks, add aerogel insulation materials into the insulation tank, add foamed ceramic panels into several cavities, and use adhesives to improve the tightness of the installation of aerogel insulation materials and foamed ceramic panels, thereby obtaining complete insulation blocks, and installing the insulation blocks with mortar to obtain a composite wall.

[0020] Preferably, the ceramic fragments in S1 are calcined at high temperature to form a closed-cell ceramic material with high porosity, which is then used to make a foamed ceramic board. In S1, the aerogel thermal insulation material is made with nano-silicon dioxide aerogel as the main material.

[0021] Preferably, the diameter of the small particles obtained by crushing in S2 should be less than 3.5 mm.

[0022] Preferably, the shearing and crushing in S3 obtains short-cut polypropylene fibers with a diameter of 7-11 μm and a length of 6-8 mm and short-cut basalt fibers with a diameter of 3-5 μm and a length of 4-7 mm.

[0023] Preferably, during the mixing and stirring process in S3, the stirring time is 80-120s and the rotation speed is 50-70rpm.

[0024] Preferably, in S4, the mixture A is obtained by a stirring machine, the stirring time is 15-25 min, and the stirring speed is 120-160 rpm.

[0025] Preferably, the mixture B is obtained in S5, and the stirring time is 15-25 min, and the stirring speed is 130-170 rpm.

[0026] Preferably, the recycled concrete material obtained in S6 has a stirring time of 10-15 min and a stirring speed of 200-240 rpm.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention adopts the arrangement of recycled concrete blocks, insulation tanks and cavities, and adds aerogel insulation materials and foamed ceramic plates into the insulation tanks and cavities. The aerogel insulation materials have low thermal conductivity, are waterproof and non-flammable, and also have the effects of sound insulation and shock absorption. The foamed ceramic plates have low thermal conductivity and non-combustibility, thereby reducing the thermal conductivity of the insulation blocks and improving the fire prevention and insulation effects.

[0029] 2. The recycled concrete blocks, aerogel insulation materials and foamed ceramic plates used in the preparation of the insulation blocks of the present invention are all recyclable environmentally friendly materials, and the aerogel insulation materials and foamed ceramic plates are installed in the insulation grooves and cavities provided on the recycled concrete blocks, so they will not be damaged or fall off due to long-term use, thereby ensuring the service life of the insulation blocks;

[0030] 3. The thermal insulation blocks made by adding polyethylene fiber and basalt fiber in the present invention have better compression resistance and demolition resistance than the thermal insulation blocks without adding polyethylene fiber or basalt fiber, which is beneficial to improve the service life of the wall made of thermal insulation blocks;

[0031] 4. The present invention can fill and repair the cracks on the surface of the recycled aggregate through the slag powder modifier, and the polyvinyl alcohol modifier can assist in filling and repairing the recycled aggregate after filling and repair, and form a protective film on the surface of the recycled aggregate, thereby improving the adhesion of the recycled aggregate and reducing water absorption, thereby improving the anti-permeability and water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is an overall schematic diagram of the present invention;

[0033] Figure 2 It is a schematic top view of the overall structure of the present invention;

[0034] Figure 3 A schematic diagram of a recycled concrete block according to the present invention;

[0035] Figure 4 It is a schematic diagram of the preparation process of the present invention.

[0036] In the figure: 1. Recycled concrete block; 2. Insulation tank; 3. Aerogel insulation material; 4. Cavity; 5. Foamed ceramic plate; 6. Connection hole; 7. Connection block; 8. Waterproof layer; 9. Wear-resistant protective layer; 10. Slot; 11. Block. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front end", "rear end", "two ends", "one end", "the other end" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0039] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0040] Example 1: Please refer to Figure 1 , Figure 2 and Figure 3 The present invention provides an embodiment: a composite wall insulation block with low thermal conductivity and a preparation method thereof, comprising a recycled concrete block 1, a heat preservation groove 2 is opened in the middle of the top of the recycled concrete block 1, and an aerogel heat preservation material 3 is installed on the inner wall of the heat preservation groove 2;

[0041] A plurality of cavities 4 are provided on the outer side of the top of the recycled concrete block 1, and a foamed ceramic plate 5 is installed on the inner wall of the cavity 4. A connection hole 6 is provided at each of the four corners of the top of the recycled concrete block 1, and a connection block 7 is installed at each of the four corners of the bottom of the recycled concrete block 1, and the inner wall of the connection hole 6 is connected to the outer wall of the connection block 7;

[0042] Another group of recycled concrete blocks 1 are installed on the top, bottom, front and side of the recycled concrete block 1 through mortar, and a heat-insulating wall is set by multiple groups of recycled concrete blocks 1. A waterproof layer 8 is installed on one side and the other side of the recycled concrete block 1. The outer wall of the waterproof layer 8 on the other side of the recycled concrete block 1 is installed with a wear-resistant protective layer 9. A group of card slots 10 are opened on the front of the recycled concrete block 1, and a group of card blocks 11 are installed on the back of the recycled concrete block 1, and the inner wall of the card slot 10 is movably connected to the outer wall of the card block 11;

[0043] Furthermore, by setting the recycled concrete blocks 1, the insulation tank 2 and the cavity 4, the aerogel insulation material 3 and the foamed ceramic plate 5 are added into the insulation tank 2 and the cavity 4. The aerogel insulation material 3 has low thermal conductivity, is waterproof and non-flammable, and also has the effects of sound insulation and shock absorption. The foamed ceramic plate 5 has low thermal conductivity and non-combustion effects, thereby reducing the thermal conductivity of the insulation blocks and improving the fire prevention and insulation effects.

[0044] The recycled concrete blocks 1, aerogel insulation materials 3 and foamed ceramic plates 5 used in preparing the insulation blocks are all recyclable environmentally friendly materials, and the aerogel insulation materials 3 and foamed ceramic plates 5 are both installed in the insulation grooves 2 and cavities 4 opened on the recycled concrete blocks 1. Therefore, they will not be damaged or fall off due to long-term use, thereby ensuring the service life of the insulation blocks.

[0045] Example 2: Please refer to Figure 4 The present invention provides an embodiment: the preparation steps of the composite wall insulation block with low thermal conductivity are as follows:

[0046] S1. Obtain raw materials for composing a composite wall insulation block with a low thermal coefficient, wherein the weight proportions of the raw materials are 50 parts of recycled aggregate, 30 parts of natural aggregate, 1 part of polyethylene fiber, 20 parts of expansion agent, 0.5 parts of dispersant, 45 parts of cement, 22 parts of water, 1 part of water reducing agent, 10 parts of slag micro powder modifier, 10 parts of polyvinyl alcohol modifier, 1 part of basalt fiber, 13 parts of ceramic fragments, 1 part of adhesive and 10 parts of nano-silica aerogel;

[0047] S2, grinding and crushing the recycled aggregate to obtain small particles, soaking the obtained particles in a slag micropowder modifier for 1 hour and then taking them out to air-dry, and then soaking the air-dried particles again in a polyvinyl alcohol modifier for 1 hour and then taking them out to air-dry, thereby obtaining the modified recycled aggregate;

[0048] S3, shearing and crushing the polyethylene fiber and the basalt fiber respectively to obtain short-cut polyethylene fiber and short-cut basalt fiber, and mixing and stirring the obtained short-cut fiber with an expansion agent and a dispersant to obtain a composite fiber anti-cracking agent;

[0049] S4, putting the recycled aggregate obtained in S2 and the natural aggregate into a mixing machine, mixing and stirring, and obtaining a mixture A;

[0050] S5, mixing the composite fiber anti-cracking agent obtained in S3 with the mixture A obtained in S4, thereby obtaining a mixture B;

[0051] S6, adding cement, water and a water reducing agent to the mixture B obtained in S5, mixing and stirring, and thereby obtaining a recycled concrete material;

[0052] S7, using recycled concrete materials to make recycled concrete blocks 1, adding aerogel insulation materials 3 into the insulation tank 2, adding foamed ceramic plates 5 into the plurality of cavities 4, and using adhesives to improve the fastness of the installation of the aerogel insulation materials 3 and the foamed ceramic plates 5, thereby obtaining complete insulation blocks, and mutually installing the insulation blocks with mortar, thereby obtaining a composite wall;

[0053] The ceramic fragments in S1 are calcined at high temperature to form a high-porosity closed-cell ceramic material, which is then used to make a foamed ceramic plate 5. The nano-silicon dioxide aerogel in S1 is used as the main material to make an aerogel thermal insulation material 3;

[0054] The diameter of the small particles obtained by crushing in S2 must be less than 3.5 mm;

[0055] The shearing and crushing in S3 obtains short-cut polypropylene fibers with a diameter of 7-11 μm and a length of 6-8 mm and short-cut basalt fibers with a diameter of 3-5 μm and a length of 4-7 mm;

[0056] During the mixing and stirring process in S3, the stirring time is 100 s and the rotation speed is 60 rpm;

[0057] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 20 min and the stirring speed is 140 rpm;

[0058] In S5, a mixture B is obtained, and the stirring time is 20 min and the stirring speed is 150 rpm;

[0059] The recycled concrete material obtained in S6 has a mixing time of 13 min and a mixing speed of 220 rpm.

[0060] Example 3: Please refer to Figure 4 The present invention provides an embodiment: the preparation steps of the composite wall insulation block with low thermal conductivity are as follows:

[0061] S1. Obtain raw materials for composing a composite wall insulation block with a low thermal coefficient, wherein the weight proportions of the raw materials are 60 parts of recycled aggregate, 40 parts of natural aggregate, 2 parts of polyethylene fiber, 23 parts of expansion agent, 0.7 parts of dispersant, 58 parts of cement, 25 parts of water, 2 parts of water reducing agent, 13 parts of slag micro powder modifier, 13 parts of polyvinyl alcohol modifier, 2 parts of basalt fiber, 15 parts of ceramic fragments, 1.5 parts of adhesive and 12 parts of nano-silica aerogel;

[0062] S2, grinding and crushing the recycled aggregate to obtain small particles, soaking the obtained particles in a slag micropowder modifier for 1 hour and then taking them out to air-dry, and then soaking the air-dried particles again in a polyvinyl alcohol modifier for 1 hour and then taking them out to air-dry, thereby obtaining the modified recycled aggregate;

[0063] S3, shearing and crushing the polyethylene fiber and the basalt fiber respectively to obtain short-cut polyethylene fiber and short-cut basalt fiber, and mixing and stirring the obtained short-cut fiber with an expansion agent and a dispersant to obtain a composite fiber anti-cracking agent;

[0064] S4, putting the recycled aggregate obtained in S2 and the natural aggregate into a mixing machine, mixing and stirring, and obtaining a mixture A;

[0065] S5, mixing the composite fiber anti-cracking agent obtained in S3 with the mixture A obtained in S4, thereby obtaining a mixture B;

[0066] S6, adding cement, water and a water reducing agent to the mixture B obtained in S5, mixing and stirring, and thereby obtaining a recycled concrete material;

[0067] S7, using recycled concrete materials to make recycled concrete blocks 1, adding aerogel insulation materials 3 into the insulation tank 2, adding foamed ceramic plates 5 into the plurality of cavities 4, and using adhesives to improve the fastness of the installation of the aerogel insulation materials 3 and the foamed ceramic plates 5, thereby obtaining complete insulation blocks, and mutually installing the insulation blocks with mortar, thereby obtaining a composite wall;

[0068] The ceramic fragments in S1 are calcined at high temperature to form a high-porosity closed-cell ceramic material, which is then used to make a foamed ceramic plate 5. The nano-silicon dioxide aerogel in S1 is used as the main material to make an aerogel thermal insulation material 3;

[0069] The diameter of the small particles obtained by crushing in S2 must be less than 3.5 mm;

[0070] The shearing and crushing in S3 obtains short-cut polypropylene fibers with a diameter of 7-11 μm and a length of 6-8 mm and short-cut basalt fibers with a diameter of 3-5 μm and a length of 4-7 mm;

[0071] During the mixing and stirring process in S3, the stirring time is 100 s and the rotation speed is 60 rpm;

[0072] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 20 min and the stirring speed is 140 rpm;

[0073] In S5, a mixture B is obtained, and the stirring time is 20 min and the stirring speed is 150 rpm;

[0074] The recycled concrete material obtained in S6 has a mixing time of 13 min and a mixing speed of 220 rpm.

[0075] Example 4: Please refer to Figure 4 The present invention provides an embodiment: the preparation steps of the composite wall insulation block with low thermal conductivity are as follows:

[0076] S1. Obtain raw materials for composing a composite wall insulation block with a low thermal coefficient, wherein the weight proportions of the raw materials are 70 parts of recycled aggregate, 45 parts of natural aggregate, 3 parts of polyethylene fiber, 25 parts of expansion agent, 1 part of dispersant, 68 parts of cement, 28 parts of water, 3 parts of water reducing agent, 16 parts of slag micro powder modifier, 16 parts of polyvinyl alcohol modifier, 3 parts of basalt fiber, 18 parts of ceramic fragments, 2 parts of adhesive and 15 parts of nano-silica aerogel;

[0077] S2, grinding and crushing the recycled aggregate to obtain small particles, soaking the obtained particles in a slag micropowder modifier for 1 hour and then taking them out to air-dry, and then soaking the air-dried particles again in a polyvinyl alcohol modifier for 1 hour and then taking them out to air-dry, thereby obtaining the modified recycled aggregate;

[0078] S3, shearing and crushing the polyethylene fiber and the basalt fiber respectively to obtain short-cut polyethylene fiber and short-cut basalt fiber, and mixing and stirring the obtained short-cut fiber with an expansion agent and a dispersant to obtain a composite fiber anti-cracking agent;

[0079] S4, putting the recycled aggregate obtained in S2 and the natural aggregate into a mixing machine, mixing and stirring, and obtaining a mixture A;

[0080] S5, mixing the composite fiber anti-cracking agent obtained in S3 with the mixture A obtained in S4, thereby obtaining a mixture B;

[0081] S6, adding cement, water and a water reducing agent to the mixture B obtained in S5, mixing and stirring, and thereby obtaining a recycled concrete material;

[0082] S7, using recycled concrete materials to make recycled concrete blocks 1, adding aerogel insulation materials 3 into the insulation tank 2, adding foamed ceramic plates 5 into the plurality of cavities 4, and using adhesives to improve the fastness of the installation of the aerogel insulation materials 3 and the foamed ceramic plates 5, thereby obtaining complete insulation blocks, and mutually installing the insulation blocks with mortar, thereby obtaining a composite wall;

[0083] The ceramic fragments in S1 are calcined at high temperature to form a high-porosity closed-cell ceramic material, which is then used to make a foamed ceramic plate 5. The nano-silicon dioxide aerogel in S1 is used as the main material to make an aerogel thermal insulation material 3;

[0084] The diameter of the small particles obtained by crushing in S2 must be less than 3.5 mm;

[0085] The shearing and crushing in S3 obtains short-cut polypropylene fibers with a diameter of 7-11 μm and a length of 6-8 mm and short-cut basalt fibers with a diameter of 3-5 μm and a length of 4-7 mm;

[0086] During the mixing and stirring process in S3, the stirring time is 100 s and the rotation speed is 60 rpm;

[0087] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 20 min and the stirring speed is 140 rpm;

[0088] In S5, a mixture B is obtained, and the stirring time is 20 min and the stirring speed is 150 rpm;

[0089] The recycled concrete material obtained in S6 has a mixing time of 13 min and a mixing speed of 220 rpm.

[0090] For comparative example 1, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that no polyethylene fiber is added.

[0091] For comparative example 2, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that basalt fiber is not added.

[0092] For comparative example 3, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that polyethylene fiber and basalt fiber are not added.

[0093] For comparative example 4, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation method is the same as that of Example 2, except that no ceramic fragments are added.

[0094] For comparative example 5, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that no nano-silica aerogel is added.

[0095] For comparative example 6, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that no slag micropowder modifier is added.

[0096] For comparative example 7, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that no polyvinyl alcohol modifier is added.

[0097] For comparative example 8, please refer to Figure 4, a comparative example provided by the present invention: the specific implementation manner is the same as that of Example 2, except that no slag micropowder modifier and polyvinyl alcohol modifier are added.

[0098] Performance test, the thermal insulation blocks prepared in Examples 2-4 and Comparative Examples 1-5 were selected as samples, and the thermal conductivity, compressive strength and demolition strength were tested respectively;

[0099] Test results: Furthermore, 1. The thermal insulation blocks made by adding polyethylene fiber and basalt fiber have better compression resistance and demolition resistance than the thermal insulation blocks without adding polyethylene fiber or basalt fiber;

[0100] By adding the foamed ceramic plate 5 and the aerogel thermal insulation material 3, it is helpful to reduce the thermal conductivity of the thermal insulation block, thereby improving the thermal insulation effect of the thermal insulation block, and the thermal conductivity of the aerogel thermal insulation material 3 is lower than that of the foamed ceramic plate 5;

[0101] The slag micropowder modifier can fill and repair the cracks on the surface of the recycled aggregate, and the polyvinyl alcohol modifier can assist in filling and repairing the recycled aggregate after filling and repair, and form a protective film on the surface of the recycled aggregate, thereby improving the adhesion of the recycled aggregate and reducing water absorption, thereby improving the anti-permeability and water resistance.

[0102] Comparative Example 9, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation is the same as that of Example 2, except that, during the mixing and stirring process in S3, the stirring time is 80s and the rotation speed is 50rpm;

[0103] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 15 min and the stirring speed is 120 rpm;

[0104] In S5, a mixture B is obtained, and the stirring time is 15 min and the stirring speed is 130 rpm;

[0105] The recycled concrete material obtained in S6 has a mixing time of 10 min and a mixing speed of 200 rpm.

[0106] Comparative Example 10, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation is the same as that of Example 2, except that, during the mixing and stirring process in S3, the stirring time is 120s and the rotation speed is 70rpm;

[0107] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 25 min and the stirring speed is 160 rpm;

[0108] In S5, a mixture B is obtained, and the stirring time is 25 min and the stirring speed is 170 rpm;

[0109] The recycled concrete material obtained in S6 has a mixing time of 15 min and a mixing speed of 240 rpm.

[0110] Comparative Example 11, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation method is the same as that of Example 2, except that, during the mixing and stirring process in S3, the stirring time is 80s and the rotation speed is 70rpm;

[0111] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 15 min and the stirring speed is 160 rpm;

[0112] In S5, a mixture B is obtained, and the stirring time is 15 min and the stirring speed is 170 rpm;

[0113] The recycled concrete material obtained in S6 has a mixing time of 10 min and a mixing speed of 240 rpm.

[0114] Comparative Example 12, please refer to Figure 4 , a comparative example provided by the present invention: the specific implementation is the same as that of Example 2, except that, during the mixing and stirring process in S3, the stirring time is 120s and the rotation speed is 50rpm;

[0115] In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 25 min and the stirring speed is 120 rpm;

[0116] In S5, a mixture B is obtained, and the stirring time is 25 min and the stirring speed is 130 rpm;

[0117] The recycled concrete material obtained in S6 has a mixing time of 15 min and a mixing speed of 200 rpm.

[0118] Performance test, the thermal insulation blocks prepared in Example 2 and Comparative Examples 6-9 were selected as samples, and the thermal conductivity, compressive strength and demolition strength were tested respectively;

[0119] Test results: Furthermore, by adjusting the stirring time and stirring speed of the stirring device, the compressive strength and the demolition strength can be slightly changed.

[0120] Working principle: through the setting of recycled concrete blocks 1, insulation grooves 2 and cavities 4, aerogel insulation materials 3 and foamed ceramic plates 5 are added to the insulation grooves 2 and cavities 4. The aerogel insulation materials 3 have low thermal conductivity, are waterproof and non-flammable, and also have the effects of sound insulation and shock absorption. The foamed ceramic plates 5 have low thermal conductivity and non-combustion effects, thereby reducing the thermal conductivity of the insulation blocks and improving the fire prevention and insulation effects. The recycled concrete blocks 1, aerogel insulation materials 3 and foamed ceramic plates 5 used to prepare the insulation blocks are all recyclable environmentally friendly materials, and the aerogel insulation materials 3 and foamed ceramic plates 5 are all installed in the insulation grooves 2 and cavities 4 opened on the recycled concrete blocks 1, so they will not be damaged or fall off due to long-term use, thereby ensuring the service life of the insulation blocks. By adding polyethylene fibers and black The insulation blocks made of basalt fiber have better compression resistance and demolition resistance than the insulation blocks without polyethylene fiber or basalt fiber. The addition of foamed ceramic board 5 and aerogel insulation material 3 is beneficial to reduce the thermal conductivity of the insulation block, thereby improving the insulation effect of the insulation block, and the thermal conductivity of the aerogel insulation material 5 is lower than that of the foamed ceramic board 3. The slag micropowder modifier can fill and repair the cracks on the surface of the recycled aggregate, and the polyvinyl alcohol modifier can assist in filling and repairing the recycled aggregate after filling and repair, and form a protective film on the surface of the recycled aggregate, thereby improving the adhesion of the recycled aggregate and reducing water absorption, thereby improving the anti-permeability and water resistance. By adjusting the stirring time and stirring speed of the stirring device, the compressive strength and demolition strength can be slightly changed.

[0121] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a composite wall insulation block with low thermal conductivity, the composite wall insulation block comprising a recycled concrete block (1), characterized in that: A heat preservation groove (2) is provided in the middle of the top of the recycled concrete block (1), and an aerogel heat preservation material (3) is installed on the inner wall of the heat preservation groove (2); A plurality of cavities (4) are provided on the outer side of the top of the recycled concrete block (1), a foamed ceramic plate (5) is installed on the inner wall of the cavity (4), connection holes (6) are provided at the four corners of the top of the recycled concrete block (1), connection blocks (7) are installed at the four corners of the bottom of the recycled concrete block (1), and the inner wall of the connection hole (6) is connected to the outer wall of the connection block (7); Another group of recycled concrete blocks (1) are installed on the top, bottom, front and side of the recycled concrete block (1) through mortar; a heat-insulating wall is provided by the plurality of groups of recycled concrete blocks (1); a waterproof layer (8) is installed on one side and the other side of the recycled concrete block (1); a wear-resistant protective layer (9) is installed on the outer wall of the waterproof layer (8) on the other side of the recycled concrete block (1); a group of slots (10) are provided on the front of the recycled concrete block (1); a group of blocks (11) are installed on the back of the recycled concrete block (1); and the inner wall of the slot (10) is movably connected to the outer wall of the block (11); The steps of the preparation method of the composite wall insulation building block are as follows: S1. Obtain raw materials for composite wall insulation blocks with low thermal coefficient, wherein the weight proportions of the raw materials are 50-70 parts of recycled aggregate, 30-45 parts of natural aggregate, 1-3 parts of polyethylene fiber, 20-25 parts of expansion agent, 0.5-1 parts of dispersant, 45-68 parts of cement, 22-28 parts of water, 1-3 parts of water reducing agent, 10-16 parts of slag micro powder modifier, 10-16 parts of polyvinyl alcohol modifier, 1-3 parts of basalt fiber, 13-18 parts of ceramic fragments, 1-2 parts of adhesive and 10-15 parts of nano-silica aerogel; S2, grinding and crushing the recycled aggregate to obtain small particles, soaking the obtained particles in a slag micropowder modifier for 1 hour and then taking them out to air-dry, and then soaking the air-dried particles again in a polyvinyl alcohol modifier for 1 hour and then taking them out to air-dry, thereby obtaining the modified recycled aggregate; S3, shearing and crushing the polyethylene fiber and the basalt fiber respectively to obtain short-cut polyethylene fiber and short-cut basalt fiber, and mixing and stirring the obtained short-cut fiber with an expansion agent and a dispersant to obtain a composite fiber anti-cracking agent; S4, putting the recycled aggregate obtained in S2 and the natural aggregate into a mixing machine, mixing and stirring, and obtaining a mixture A; S5, mixing the composite fiber anti-cracking agent obtained in S3 with the mixture A obtained in S4, thereby obtaining a mixture B; S6, adding cement, water and a water reducing agent to the mixture B obtained in S5, mixing and stirring, and thereby obtaining a recycled concrete material; S7. Use recycled concrete materials to make recycled concrete blocks (1), add aerogel insulation materials (3) into the insulation tank (2), add foamed ceramic panels (5) into the plurality of cavities (4), and use adhesives to improve the tightness of the installation of the aerogel insulation materials (3) and the foamed ceramic panels (5), thereby obtaining complete insulation blocks, and mutually installing the insulation blocks with mortar, thereby obtaining a composite wall.

2. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: The ceramic fragments in S1 are calcined at high temperature to form a high-porosity closed-cell ceramic material, which is then used to make a foamed ceramic plate (5). The aerogel thermal insulation material (3) in S1 is made with nano-silicon dioxide aerogel as the main material.

3. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: The diameter of the small particles obtained by crushing in S2 must be less than 3.5 mm.

4. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: The shearing and crushing in S3 obtains short-cut polypropylene fibers with a diameter of 7-11 μm and a length of 6-8 mm and short-cut basalt fibers with a diameter of 3-5 μm and a length of 4-7 mm.

5. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: During the mixing and stirring process in S3, the stirring time is 80-120s and the rotation speed is 50-70rpm.

6. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: In S4, a mixture A is obtained by a stirring machine, wherein the stirring time is 15-25 min and the stirring speed is 120-160 rpm.

7. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: In the step S5, the mixture B is obtained, and the stirring time is 15-25 min, and the stirring speed is 130-170 rpm.

8. The method for preparing a composite wall insulation block with low thermal conductivity according to claim 1, characterized in that: The recycled concrete material obtained in S6 has a stirring time of 10-15 min and a stirring speed of 200-240 rpm.

Citation Information

Patent Citations

  • Steam-free self-insulating block and preparation method thereof

    CN104402493B

  • Block for constructing wall and construction wall thereof

    KR101830354B1

  • Wall construction and component for the same

    US8806824B2

  • Self-reinforced masonry blocks, walls made from self-reinforced masonry blocks, and method for making self-reinforced masonry blocks

    US9175469B2

  • Sawtoothed lightweight concrete heat insulation composite building block, formula and preparation method of composite building block

    CN107098720A